Freeze-dried allograft-mediated gene or protein delivery of growth and differentiation factor 5 reduces reconstructed murine flexor tendon adhesions. (19th March 2014) - Hasslund, Sys; Dadali, Tulin; Ulrich-Vinther, Michael; Søballe, Kjeld; Schwarz, Edward M; Awad, Hani A
Advances in allograft processing have opened new horizons for clinical adaptation of flexor tendon allografts as delivery scaffolds for antifibrotic therapeutics. Recombinant adeno-associated-virus (rAAV) gene delivery of the growth and differentiation factor 5 (GDF-5) has been previously associated with antifibrotic effects in a mouse model of flexor tendoplasty. In this study, we compared the effects of loading freeze-dried allografts with different doses of GDF-5 protein or rAAV- Gdf5 on flexor tendon healing and adhesions. We first optimized the protein and viral loading parameters using reverse transcription polymerase chain reaction (RT-PCR), enzyme-linked immunosorbent assay (ELISA), and in vivo bioluminescent imaging. We then reconstructed flexor digitorum longus (FDL) tendons of the mouse hindlimb with allografts loaded with low and high doses of recombinant GDF-5 protein and rAAV- Gdf5 and evaluated joint flexion and biomechanical properties of the reconstructed tendon. In vitro optimization studies determined that both the loading time and concentration of the growth factor and viral vector had dose-dependent effects on their retention on the freeze-dried allograft. In vivo data suggest that protein and gene delivery of GDF-5 had equivalent effects on improving joint flexion function, in the range of doses used. Within the doses tested, the lower doses of GDF-5 had more potent effects on suppressing adhesions without adversely affecting the strength of the repair. These findings indicate equivalent antifibrotic effects of Gdf5 gene and protein delivery, but suggest that localized delivery of this potent factor should also carefully consider the dosage used to eliminate untoward effects, regardless of the delivery mode.